Improvements in grain and fodder yield of cowpea (Vigna unguiculata) varieties developed in the Sudan savannas of Nigeria over the past four decades - Kamara, A.Y.; Ewansiha, S.U.; Ajeigbe, Hakeem A.; Okechukwu, R.U.; Tefera, H.; Boukar, O.; Omoigui, L.O. (International Institute of Tropical Agriculture, 2012)
A field study was conducted to determine the rate of genetic improvement in grain and fodder yields of cowpea genotypes developed in the Nigerian Sudan savannas from 1970 to 2004. Results showed that grain yield ranged from 568 kg/ha for an old variety TVX3236 to 1851 kg/ha for a recently released variety IT04K-321-2. The average rate of increase has been 28 kg/ha/year, which corresponds to a genetic gain of 3.6%. Fodder yield ranged from 1363 kg/ha for a variety released in 1976 (TVX1836-0131) to 3346 kg/ha for IT98k-476-8 released in 1998 corresponding to a genetic gain of 1.96%. This indicated that selection for dual-purpose cowpea varieties with increased fodder as well as grain yields has been successful. Total dry matter, fodder yield, harvest index, and 100-seed weight were significantly correlated with grain yield. The strong relationship between grain and fodder yields showed the success made in selecting for dual-purpose cowpea varieties.